PENINGKATAN KETERAMPILAN KOMUNIKASI INTERPERSONAL MELALUI TEKNIK DISKUSI KELOMPOK PADA SISWA KELAS VIII SMP NEGERI 1 WATES DAN SMP NEGERI 3 WATES YOGYAKARTA - Endah Rahmawati; Muh Farozin (Jurnal Ilmiah Didaktika, 2019)
This study aimed to improve final year students of SMP Negeri 1 and SMP Negeri 3 Wates’ interpersonal communication skills through group discussion techniques. Classroom action research was conducted by using Kemmis and Taggart model.. The instrument of data collection used was observation guidelines and interpersonal communication skills’ scale. The results showed that the improvement of interpersonal communication skill of class VIII students of SMP Negeri 1 Wates and SMP Negeri 3 Wates could be done by using group discussion technique. This is evidenced by the increase in the average value of interpersonal communication skills. In the first cycle, the class VIII students of SMP Negeri 1 Wates increased by 43.8 points, while in the second cycle improved up to 74.7 points. For the class VIII students of SMP Negeri 3 Wates, the increase in first cycle was 26.5 points, while in the second cycle it was 75.7 points.